The Role of Job Satisfaction in Mediating the Effect of Work-Life Balance on Turnover Intention among Sales Employees at Fifgroup Cirebon - Cici Sunarci; Anna Suzana (Indonesian Journal of Business Analytics, 2026)
The research investigates how job satisfaction functions as an intermediary in the relationship between work–life balance and employees’ intention to leave, focusing on sales staff at FIFGROUP in Cirebon. A quantitative method with an associative framework was applied. The sample consisted of 109 participants selected through purposive sampling, with the size determined using the Slovin formula. Data collection was conducted באמצעות a structured questionnaire using a Likert scale, and the analysis employed SEM-PLS techniques. The findings indicate that a better work–life balance contributes positively to higher levels of job satisfaction, while simultaneously decreasing the likelihood of turnover intention. In addition, job satisfaction itself is found to reduce employees’ intention to resign and plays a mediating role in the relationship between the two variables. Overall, the study highlights that organizational efforts to improve work–life balance.